Problem Solution of Using Wastes in Technology of Building Materials - Saidmuratov, B. I.; M., Mamatov (European Journal of Life Safety and Stability (2660-9630), 2022)
At present, the problem of utilization of industrial and domestic waste is on the agenda as a critical issue in all countries of the world. According to the data studied by scientists, such wastes in cities account for an average of 1 ton per capita, of which at least 50-80 kg is solid household waste. In addition, the decay of different grains varies, for example, it takes 2-10 years for paper grains to decompose. Similarly, it takes at least 100 years for coffee, canned and other cans, up to 500 years for polyethylene and plastic cans, and at least 1,000 years for glassware to completely decompose.